The growing story of (ARABIDOPSIS) CRINKLY 4 - Czyzewicz, Nathan; Nikonorova, Natalia; Meyer, Matthew R.; Sandal, Priyanka; Shah, Shweta; Vu, Lam Dai; Gevaert, Kris; Rao, A. Gururaj; De Smet, Ive (Oxford University Press, 2016)
Receptor kinases play important roles in plant growth and development, but only few of them have been functionally characterized in depth. Over the past decade CRINKLY 4 (CR4)-related research has peaked as a result of a newly discovered role of ARABIDOPSIS CR4 (ACR4) in the root. Here, we comprehensively review the available (A)CR4 literature and describe its role in embryo, seed, shoot, and root development, but we also flag an unexpected role in plant defence. In addition, we discuss ACR4 domains and protein structure, describe known ACR4-interacting proteins and substrates, and elaborate on the transcriptional regulation of ACR4. Finally, we address the missing knowledge in our understanding of ACR4 signalling.